IDENTIFICATION OF WASTE FROM FISHING VESSEL BASED AT THE BITUNG OCEAN FISHING PORT - Putri, Elsari Tanjung; Manohas, Jul; Simau, Silvester; Manengkey, Jenny I.; Saranga, Rudi; Darondo, Franky A.; Katili, Lidya; Karyanto, Karyanto (Jurnal Segara, 2024)
One source of marine pollution can be caused by the operational activities of fishing vessels. This research aims to identify the type and amount of waste originating from fishing vessels. Data collection was conducted at Bitung Ocean Fishing Port during November-December 2023 by purposive sampling. The waste that has been collected, sorted and weighed. Data were analysed using descriptive quantitative. The waste generated by fishing vessels consists of two types, namely organic and inorganic waste. Organic waste consists of food waste and kitchen waste, while inorganic waste consists of 70% plastic, 12% processed wood, 10% glass, 6% clothing or cloth, and 1% metal and rubber. Organic waste is disposed of directly into the sea, while inorganic waste is collected in storage containers for later disposal on land. There is a need for more action in fishery vessel waste management, such as training in recycling that can generate economic benefits, in an effort to reduce waste from fishing vessels.